Barriers to physical health care in persons with severe mental illness: a facility based mixed method study in Ethiopia - Merga, Desalegn Bekele (Department of Psychiatry and Mental Health, 2015)
People with severe mental illnesses (SMI) face barriers that contribute to poor physical health outcomes. However, these barriers have not been systematically investigated in Ethiopia. Aim: The aim of this study was to examine barriers to care for physical co-morbidities among SMI patients. It achieves this by: i) estimating the prevalence of physical co-morbidities in SMI in-patients in a psychiatric referral hospital over a two month period; ii) describing potential associations of various socio-demographic and clinical factors with the occurrence of physical co- morbidities in admitted patients with SMI; and iii) exploring barriers in recognition and management of these physical comorbidities in the immediate curative medical care environment of admitted SMI patients in the psychiatric referral hospital. Methods: The study used a mixed methods design that included: i) a quantitative cross-sectional facilitybased record review; and ii) a qualitative exploration of potential or experienced barriers to physical health care provision by patients, caregivers, mental and general health professionals. The quantitative component estimated prevalence and examined risk factors associated with the presence of co-morbid physical health conditions among people with SMI. For this, clinical records of all admitted patients with diagnosis of SMI were reviewed over a two-months period. To check the reliability of the clinical records, a pilot test was done for two weeks before actual data collection. By using systematic random sampling of the records reviewed, 30 patients were selected for physician assessment in order to check the accuracy of the information included in records. The qualitative section was conducted using semistructured interviews with SMI patients and their caregivers and focus group discussions with service providers.